Empirics of Human Development in India, 1990–2015. Issue 2 (August 2019) - Chaurasia, Aalok Ranjan
This article uses the annual estimates of the human development index (HDI) prepared by the Global Data Lab of the Radboud University of The Netherlands to analyse the progress of human development in India during 1990–2015. The analysis reveals that human development in the country remains comparatively low by global standards and there are considerable variations in human development across states/union territories, although there is evidence of convergence in human development across states/union territories. The decomposition of the improvement in the HDI indicates that the progress in human development in the country has primarily been the result of the progress in the education dimension whereas the contribution of the progress in the dimension of health or well-being has been the smallest. The article calls for redesigning the National Sample Survey to generate data necessary for the estimation of the HDI on an annual basis at national and state/union territory level.